Nitrimidazine Compared with Metronidazole in the Treatment of Vaginal Trichomoniasis - Evans, B. A. (1971)
A new substituted nitroimidazole, nitrimidazine (Naxogin), is compared with the established drug, metronidazole (Flagyl), for the treatment of vaginal trichomoniasis in a randomized double-blind trial. Nitrimidazine cured 39 (68%) out of 57 patients and showed no undesirable effects other than nausea in one patient. Metronidazole cured 51 (89%) out of 57 patients and also caused nausea in one patient; this cure rate corresponds with that previously reported in other trials. In the recommended dosage nitrimidazine is inferior to metronidazole, but is sufficiently effective to be useful in cases of intolerance to metronidazole.